2008
DOI: 10.1186/1471-2407-8-16
|View full text |Cite
|
Sign up to set email alerts
|

Augmented serum level of major histocompatibility complex class I-related chain A (MICA) protein and reduced NKG2D expression on NK and T cells in patients with cervical cancer and precursor lesions

Abstract: Background: Cervical cancer is the second most common cancer in women worldwide. NK and cytotoxic T cells play an important role in the elimination of virus-infected and tumor cells through NKG2D activating receptors, which can promote the lysis of target cells by binding to the major histocompatibility complex class I-related chain A (MICA) proteins. Increased serum levels of MICA have been found in patients with epithelial tumors. The aim of this study was to compare the levels of soluble MICA (sMICA) and NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 61 publications
1
64
1
1
Order By: Relevance
“…Indeed, soluble forms of NKG2DLs are present in the serum of cancer patients, and their levels correlate with tumor stage and metastasis (12,20,21,(38)(39)(40)(41), as well as with reduced expression of NKG2D on NK cells and other cytotoxic lymphocytes (11,21,42).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, soluble forms of NKG2DLs are present in the serum of cancer patients, and their levels correlate with tumor stage and metastasis (12,20,21,(38)(39)(40)(41), as well as with reduced expression of NKG2D on NK cells and other cytotoxic lymphocytes (11,21,42).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, elevated serum levels of soluble MICA, (19,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) MICB (20,25,29,32) and ULBP2 (21,27) have been detected in cancer patients. In addition, several clinical studies have suggested a correlation between the level of soluble MICA (sMICA) and a poor prognosis.…”
Section: Ul16-binding Protein 2 (Ulbp2) Is One Of the Ligands For Nkgmentioning
confidence: 99%
“…In addition, HPV is able to decrease the secretion of the chemokine IL-8 as well as to diminish the synthesis of IFN-␥ (12). Furthermore, it has been reported that HPV infection is associated with a reduction in the expression of different innate immune receptors, including Tolllike receptor 9 (TLR9) (9), NKp30, NKp46, and NKG2D, diminishing the cytotoxic activity NK cells (2,7). Finally, HPV is also able to inhibit the expression of the zeta chain of T cell receptor complex (CD247) and to induce the release of IL-10, interfering with the activation of Th1 lymphocytes (27,28).…”
mentioning
confidence: 99%